2015
DOI: 10.1007/s11010-015-2449-4
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular angiotensin (1–7) increases the inward calcium current in cardiomyocytes. On the role of PKA activation

Abstract: The influence of intracellular administration of angiotensin (1-7) (Ang 1-7) on the inward calcium current was investigated in myocytes isolated from the left ventricle of Wistar Kyoto rat hearts using the patch-clamp technique. The results indicated: (1) the intracellular administration of Ang (1-7) (100 nM) enhanced the peak inward calcium current (I Ca); (2) the intracellular administration of A779 (100 nM) which a Mas receptor inhibitor, abolished the effect of Ang (1-7) on the calcium current; (3) the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…After 4 min of perfusion, Ang-(1-9) induced a significant increase in developed pressure with a concomitant elevation in dP/dt max , confirming a positive inotropic response to Ang-(1-9) (Figure 7). Since protein kinase A (PKA) has been previously reported to modulate calcium flux via the L type Ca 2+ channel following application of Ang-(1-7) (24), we used the inhibitor H-89, which did indeed abolish the response to Ang-(1-9), thus supporting a role for PKA in the positive inotropic effect of Ang-(1-9).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…After 4 min of perfusion, Ang-(1-9) induced a significant increase in developed pressure with a concomitant elevation in dP/dt max , confirming a positive inotropic response to Ang-(1-9) (Figure 7). Since protein kinase A (PKA) has been previously reported to modulate calcium flux via the L type Ca 2+ channel following application of Ang-(1-7) (24), we used the inhibitor H-89, which did indeed abolish the response to Ang-(1-9), thus supporting a role for PKA in the positive inotropic effect of Ang-(1-9).…”
Section: Resultsmentioning
confidence: 81%
“…We demonstrated a direct inotropic effect of Ang-(1-9), mediated through increasing Ca 2+ transient amplitude leading to increased contraction, and possibly explained via increased L-type Ca 2+ influx paralleled by increased SR Ca 2+ content. Although a direct inotropic effect of Ang-(1-9) has not been reported previously, when Ang-(1-7) is applied intracellularly to cardiomyocytes, PKA is activated, leading to increased L-type Ca 2+ channel activity (24). Ang II is reported to increase Ca 2+ transient amplitude and intracellular Ang II is reported to increase Ca 2+ transient amplitude via modulating L-type Ca 2+ current and releasing SR Ca 2+ 43, 44.…”
Section: Discussionmentioning
confidence: 90%
“…Past reports regarding the direct effects of Ang-(1–7) on intracellular Ca 2+ mobilization in HF myocytes are conflicting. (12;18;19) One previous study indicated that acute Ang-(1–7) treatment does not modulate intracellular Ca 2+ handling in normal wild-type cardiomyocytes. (12) Consistent with that work, in the current investigation, Ang-(1–7) failed to alter the [Ca 2+ ] iT in normal myocytes of SD rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the direct effect of Ang-(1–7) on intracellular Ca 2+ mobilization in myocytes is unclear, since previous studies provided conflicting findings. (12;18;19) Furthermore, the ever-emerging body of experimental evidence continues to support that an important subset of cardiovascular actions of Ang-(1–7) is related to its bradykinin (BK) potentiating activity and its facilitation of nitric oxide (NO) release. (6;8;12;20;21) It is reasonable to speculate that the effects of Ang-(1–7) on myocyte may via Ang-(1–7) receptors while be coupled with NO/BK-mediated mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that Ang-(1–7) could stimulate protein kinase A (PKA) production via the activation of MasR, which was followed by an enhanced calcium current in the heart. This mechanism thought to regulate calcium homeostasis and improve heart contractility [ 39 ]. Furthermore, Xu et al reported that administration of Ang-(1–7) could reverse the LPS-induced reduction of α-myosin heavy chain (MHC) and β-MHC, and increase levels of S100 calcium binding protein A8 (S100A8) and S100A9 in the mouse left ventricle and finally ameliorate ventricular contractility [ 34 ].…”
Section: Discussionmentioning
confidence: 99%